Respuesta :

Answer:

t = 74 / 9

Step-by-step explanation:

-9(t - 2) = 4(1 - 15)

-9t + 18 = 4 - 60

-9t + 18 = -56

 -18      -18

-9t = -74

/-9     /-9

t = 74 / 9

t = 8.22

Answer:

t = 74 / 9 ~= 8.222

Step-by-step explanation:

-9 ( t - 2 ) = 4 ( 1 - 15 )

-9 * t + -9 * -2 = 4 * 1 + 4 * -15

-9t + 18 = 4 + -60

-9t + 18 = -56

-9t = -56 + -18

-9t = -74

t = 74 / 9

Alternatively:

-9 ( t - 2 ) = 4 ( 1 - 15 )

-9 * t + -9 * -2 = 4 ( - 14 )

-9t + 18 = -56

-9t = -56 + -18

-9t = -74

t = 74 /9

Cheers.